Bacteriernia during mastoidectorny and/or tympanoplasty - Keles, E; Kizirgil, A; Kaygusuz, I; Karlidag, T; Yalçin, S; Alpay, HC; Demir, YS (Mosby, Inc, 2005)
OBJECTIVE: To investigate the risk of bacteriemia development during surgery in patients who underwent mastoidectomy and/or tympanoplasty for chronic otitis media. PATIENTS AND METHODS: A total of 59 patients with chronic otitis media who were undergoing tympanoplasty operation with or without mastoidectomy were enrolled in this study. Smear cultures were obtained from outer ear canal and/or middle ears of all patients before the operation. Venous blood samples were obtained before and after the operation for bacteriologic analysis. Smear cultures were also obtained from the pressure dressing material that was applied during the operation for retrieval of the outer ear canal pressure. RESULTS: There was a 13.5% difference between the outer ear canal and/or middle ear smear cultures and ear pressure dressing smear cultures of the same case. There was no growth in the blood cultures obtained before tympanoplasty in any of the involved cases, however, in 5 (8.4%) of the culture samples obtained immediately after the tympanoplasty operation, there was bacteriemia. In the pressure dressing smear cultures obtained after the operation, 11 patients had microbial growth. CONCLUSION: Risk of bacteriemia should be considered in the preoperative period for the patients undergoing mastoidectomy especially in patients with cardiovascular diseases, this is of importance for the dramatic consequences that might arise after the operation. We also think that bacteriemia is also one of the factors that influences graft success rate. (C) 2005 American Academy of Otolaryngology.
Keywords: Chronic Otitis-Media; Ear Surgery; Bacteremia; Tonsillectomy; Complications; Septoplasty